ANALISIS BENTUK TINDAK TUTUR LOKUSI, ILOKUSI, PERLOKUSI DALAM NOVEL PENYALIN CAHAYA KARYA LUCIA PRIANDARINI - Lista Ameria; Abdul Malik; Fabio Testy Ariance Loren; Musliha; Maulida Mustado (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe locutionary, illocutionary, and perlocutionary speech acts in the novel Penyalin Cahaya by Lucia Priandarini. The method used in this research is descriptive with a qualitative approach. The research instrument is the researcher themselves, along with a data analysis guide table. The data collection techniques used are reading and note-taking. The results of the study found a total of eighty-three locutionary speech act data, consisting of forty-eight declarative locution data, twenty-six interrogative locution data, and six imperative locution data. Then, twenty-five illocutionary speech acts were found, including thirteen verdictive illocution data, one exersitive illocution data, one commissive illocution data, five behabitives illocution data, and five expositive illocution data. Meanwhile, eighteen perlocutionary data were found.